A determination method of defrosting start time with frost accumulation amount tracking in air source heat pump systems. (5th February 2021) - Chung, Yoong; Na, Sun-Ik; Yoo, Jin Woo; Kim, Min Soo
Highlights: A novel deforsting control method has been suggested and evaluated. The method achieves high reliability only with common sensor information. Key factors that determine the densificaton rate of the frost layer are identified. Abstract: In this paper, a novel determination method of defrosting start time based on frost accumulation amount tracking (FAAT) is proposed for air source heat pump systems. This method keeps tracking of the amount of newly deposited frost every time step using typical sensors adopted in the commercial heat pump systems. This is to predict the current volumetric blockage ratio in real-time and determine the defrosting start time. To develop the method, firstly, the reliability of the prediction results is validated with experimental data. Then, the feasibility of the suggested determination method is evaluated under various air ambient and system operating conditions. The result shows that the determination method has a root mean square error of 6.2% on a time basis and 5.1% on a capacity basis. Lastly, the influence of non-uniform frost distribution on the evaporator is investigated. It is shown that the determination method attains the robustness under varying frost non-uniformity.